Combined treatment of heat shock and glycine betaine recovered chilling injury in banana fruit by reducing membrane damage - Nadia Niaz; Wanfeng Hu; Siyi Pan; Khubaib Ali; Noman Walayat; Isam A. Mohamed Ahmed; Sobia Niaz; Jiao Zhang; Yinping Cao (Food Chemistry: X)
This study evaluated the effects of hot air (HA), hot water (HW), glycine betaine (GB), and their combination (GB + HWT) on alleviating chilling injury (CI) in unripe and ripe bananas exposed to cold stress, with treatments applied pre-ripening to asses recovery during subsequent storage. Bananas were chilled at 7 °C for 2 h, transferred to 20 °C storage, and treated with ethephon on the 12th day to induce ripening. Analyses were conducted periodically until the 21st day of storage. The combined HWT + GB treatment (T3) markedly reduced CI symptoms by preserving membrane stability and lowering oxidative stress markers like malondialdehyde and thiobarbituric acid reactive substances. Enzyme assays revealed decreased lipase, lipoxygenase, and ascorbate oxidase activities, which contributed to reduced lipid peroxidation and stabilized cell membranes. Simultaneously, increased activities of phenylpropanoid pathway enzymes, cinnamate 4-hydroxylase, and 4-cumarate CoA ligase, enhanced phenolic and flavonoid levels, contributing to antioxidant capacity. Scanning electron microscopy confirmed improved tissue integrity. Overall, GB + HWT proved to be an effective postharvest strategy for maintaining banana quality after cold exposure.